The Oil and Gas Terms in Encyclopedic Dictionaries - Jamalova Dilafruz Komiljon Qizi (Journal of Indigenous Culture, Tourism, and Language, 2026)
Purpose: This study examines how encyclopedic dictionaries interpret oil and gas terminology and how they differ from explanatory dictionaries in terms of conceptual structure and scientific depth. Research Methodology: This study used a qualitative comparative approach to analyze selected oil and gas terms in Uzbek and foreign encyclopedic dictionaries, both printed and digital versions. Definitions were examined descriptively to assess their structure, depth, and conceptual orientation through document analysis and theoretical review without using statistical software or surveys. Results: The findings indicate that encyclopedic dictionaries provide more detailed, systematic, and scientifically grounded interpretations of oil and gas terminology than explanatory dictionaries. Definitions in encyclopedic sources include interdisciplinary perspectives, technical descriptions, and contextual information related to geology, engineering, chemistry, and industrial processes. This demonstrates that encyclopedic dictionaries emphasize conceptual systems rather than simplified lexical definitions. Conclusions: This study concludes that encyclopedic dictionaries play a crucial role in the scientific and practical interpretation of oil and gas terminology. Unlike explanatory dictionaries, they present terms within broader conceptual and interdisciplinary frameworks, making them more suitable for academic and professional use than explanatory dictionaries. Limitations: This study is limited to selected encyclopedic dictionaries in Uzbek and foreign sources and does not include a large-scale corpus-based analysis or a user-centered evaluation. Contributions: This study contributes to lexicography and terminology studies by clarifying the differences between encyclopedic and explanatory dictionaries in technical fields. It benefits lexicographers, translators, educators, and oil and gas professionals who require systematic and concept-based interpretations of specialized terms.